(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: We assessed cognitive function by using different colours. Colour has been used in different neuropsychology tests for diagnostic and therapeutic purposes. Purposes: As male and female hormones are different, it is important to investigate the effect of different colours on the male and female groups for planning their therapeutic strategy in different diseases. Methods: This prospective study was done between 2012 and 2014. We used the 128-sensor net for an event related potential (ERP) study in male and female groups (n= 22 in each group). Different colours were used as stimuli. Subjects pressed ‘button 1’ when they liked the colour and ‘button 2’ when they disliked it. Reaction time (RT) and differences in like and dislike stimuli were analysed. The values of the mean differences of like and dislike stimuli were calculated using a 10-20 electrode system of 19 electrodes. The amplitudes and latencies of the N200 and P300 ERP components were analysed. Results: No significant differences were found in the mean differences of the amplitudes and latencies of the N200 and P300 ERP components between the male and female groups across 19 electrode sites. RTs were non-significantly longer in the male group. However, colour reflected on the frontal-right occipital area in the female group and the frontal-left occipital area in the male group. Conclusion: There might be a possibility of delayed decision-making due to difficulty assessing emotion in the male group compared with the female group. Bangladesh Journal of Medical Science Vol.17(4) 2018 p.612-618